Fragmentations pentecôtistes à l’île de La Réunion. Discours des origines - Valérie Aubourg (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Pentecostalism has been expanding on Réunion Island since 1966, under the aegis of the Assemblies of God. From 1983, new self-organised groups have been created. Studying this growth of new communities we look at how the leaders use of the beginnings to justify their religious action.